Estágio supervisionado e pesquisa: Perspectivas e dilemas de uma experiência - Sabino, Isabel (2018)
This article argues the contributions of Supervised Internship for the researcher teacher.The paper was conducted through an experience of approximation between teaching and researching developed in the framework of the course Supervised Internship, in Pedagogy Major, of a public university located in northeast Brazil. The discussion surrounds questions on the contribution of this course for the research training of the licensee, facilitating the promotion of the critical attitude of reflecting. The data from qualitative and empirical research, which involved teachers of the major, indicates the complexity of this subject and its contributions to the formation of the researcher professor. We recognize this as an opportunity to have contact with investigative experiences that can be understood as a collective challenge for the teachers, considering that some isolated experiences of internship that reinforce its instrumental features still exist.